Motor imagery: if you can't do it, you won't think it. - Olsson, C.-J.; Nyberg, I. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Since long, motor imagery has been recognized as a method for studying motor representations. In the last few years, important advances regarding the use of motor imagery have been made. In particular, issues concerning the functional equivalence between imagery and action have been addressed, and how equivalence affects the use of imagery to study motor representations. In this paper, we review recent findings in order to highlight the current state of knowledge about motor imagery and its relation to motor action. Three topics are discussed: (i) the imagery perspective, (ii) task complexity, and (iii) the importance of physical experience. It is shown how theses factors are closely related and how previous studies may have underestimated to what extent these factors affect the interpretation of results. Practical implications for imagery interventions are considered. It is concluded that if you cannot perform an action physically, you cannot imagine it in a way that is necessary for a high degree of functional equivalence.